Potensi Ampas Tahu Terhadap Produksi Maggot (Hermetia illucens) sebagai Sumber Protein Pakan Ikan: Potential of Tofu Dregs on the Production of Maggot (Hermetia illucens) as a Source of Protein of Fish Feed - Cicilia, Asi Pebrina; Susila, Nyata (Anterior Jurnal, 2018)
The purpose of this study was to determine the combination of media tofu and feces chicken was good against maggot production. As for the benefits of this research was to determine the percentage of tofu and feces chicken is the best of the amount of production maggot. As well as resources for fish farmers in doing maggot farming as an alternative feed. This study uses a completely randomized design (RAL) with 4 treatments three replications. The treatment used is as follows: Treatment A: tofu 100% and EM4, Treatment B: tofu 50% feces chicken 50%, Treatment C: tofu 50% feces chicken 25%, and rice bran 25%, Treatment D: tofu 50% feces chicken 25% rice bran 25%, and EM4. The results of the study media combinations tofu, feces chicken, bran and EM4 on the terms of the results of variant analysis (ANOVA) showed that the combination of media in treatment D tofu 50% feces chicken 25% rice bran 25% and EM4, resulting in an average production of maggot best is 13.73 grams, while the results of a further test with Duncan's multiple range test multiple range tests showed that there was a very real difference to the weight of maggot production between the combination used in the study. Nutrient content of maggot with crude protein 9.11% w/w, water 73.69% w/w, and crude fat 17.11% w/w for fresh maggot and nutrient content of maggot flour for crude protein 31.30% w/w, water 0.79% w/w and crude fat 34.36% w/w.